Nurses’ Experiences in Assisting Elderly with Eating Activities in Nursing Homes - Rizky Putra Prihatama; Ah Yusuf; Dianis Wulan Sari; Hilda Mazarina Devi, S.Kep., Ns., M. Sc (SCOPUS ID : 57221912497), (SINTA ID : 6784310); Nurul Imam (Universitas Tribhuwana Tunggadewi, 2025)
The experiences of nurses in assisting the elderly require considerable attention and time, particularly in fulfilling meal-related needs. Aging is accompanied by a decline in physiological functions, which can affect the ability of the elderly to eat independently. The purpose of this study was to explore nurses’ experiences in assisting older adults with eating activities. This study employed a descriptive qualitative design with a phenomenological approach. A total of eight nurses were selected using purposive sampling technique. The research was conducted in seven nursing homes located in East Java Province. Data were collected through in-depth interviews guided by structured interview questions and supported by field notes. The data were analyzed using Colaizzi’s method with the aid of the QDA Miner Lite application tool. Four major themes emerged from data analysis: 1) Assessment of the Eating Ability of the Elderly in Nursing Homes, 2) Nurses’ Experiences in Feeding the Elderly including determinants such as type of food, eating frequency, and meal times, 3) Incidence of choking among the elderly caused by swallowing disorders, age-related factors and body positioning, 4) Feeding challenges among the elderly including decreased appetite, food selectivity, dissatisfaction with meals, texture modification needs, food mixtures, slow eating pace and the need for additional snacks. A comprehensive understanding of nurses’ experiences in assisting the elderly individuals during feeding activities is essential for improving appetite and maintaining adequate nutritional intake among older adults.